Unique but diverse: some observations on the formation, structure and morphology of halloysite. (2nd January 2018) - Jock Churchman, G.; Pasbakhsh, P.; Lowe, D.J.; Theng, B.K.G.
Abstract: New insights from the recent literature are summarized and new data presented concerning the formation, structure and morphology of halloysite. Halloysite formation by weathering always requires the presence of water. Where substantial drying occurs, kaolinite is formed instead. Halloysite formation is favoured by a low pH. The octahedral sheet is positively charged at pH < ∼8, whereas the tetrahedral sheet is negatively charged at pH > ∼2. The opposing sheet charge would facilitate interlayer uptake of H2O molecules. When halloysite intercalates certain polar organic molecules, additional ( hkl ) reflections appear in the X-ray diffraction pattern, suggesting layer re-arrangement which, however, is dissimilar to that in kaolinite. Associated oxides and oxyhydroxides of Fe and Mn may limit the growth of halloysite particles as does incorporation of Fe into the structure. Particles of different shape and Fe content may occur within a given sample of halloysite.